Case Study : Amran Seri Enterprise / Syazlina Akmar Amran - Amran, Syazlina Akmar (2020)
This case study is an attempt to know how the theories can be applied to practical situation. As a student in UiTM Kota Bharu, it is a part of the study and everyone must undergo a case study project. In this case study I got the opportunity to do some research on a company which is a grocery store located at Pasir Mas, Kelantan. The first part of this project report explained the general information of the company that has been collected by interviewing the owner of the Amran Seri Enterprise and the observation of the company operation. The second part of the report contains the specialized subject study. Objective of the project is to work on the background, organizational structure, products and services that provided by Amran Seri Enterprise. Next, I studied about the technology used by this company for delivery of cooking gas. I also studied about the business, marketing of the company and its operational strategy in promoting their products. Lastly, I have done some research about the company’s financial achievements regarding how they manage their financial as well as the achievements that they gained from the financial management